The Application of Nanomaterials with in Farming Industry (International Journal of Innovative Research in Engineering & Management, 2023)
Nanomaterials having at least one  exterior dimension of 1 to 100 nanometers are classed as  materials. Nanomaterials may arise or develop naturally  or be manufactured to perform a particular function as  by-products of combustion processes. The physical and  chemical characteristics of these materials may differ  from the counterparts of their bulk form. As a  consequence of recent technical developments,  nanomaterials of different sizes and forms were produced.  These discoveries will serve as a basis for future  engineering to develop new characteristics suited to  specific applications. Nanomaterials have been utilized in  a number of previous sectors, including food production,  environmental research and medical, in an effective and  secure manner. In the scientific community, however, the  application in agriculture is under-explored, especially in  plant conservation and processing. Nanomaterials are,  according to early study, capable of improving plant  safety, germination and development in seeds,  identification of pathogens and detection of  pesticide/herbicide residues. This research covers the  agricultural uses of nanomaterials and their pros
Keywords: Agriculture; Germination; Nanomaterials; Nanoparticles; Nanotechnology